Analisis Komparatif Kinerja Ekonomi Usaha Budidaya Rumput Laut Kappaphycus alvarezii di Desa Tablolong dan Desa Oenaek, Kabupaten Kupang, Nusa Tenggara Timur - Jeli Boboi; Priyo Santoso; Ridwan Tobuku (Nusa Cendana University, 2026)
This study aimed to analyze the economic performance of Kappaphycus alvarezii seaweed farming in Tablolong Village and Oenaek Village, Kupang Regency, East Nusa Tenggara, Indonesia. Kappaphycus alvarezii has significant economic potential, particularly in the export market, due to its high carrageenan content. The study employed a quantitative approach using a descriptive and comparative research design. Data were collected through interviews, field observations, and structured questionnaires administered to seaweed farmers in both villages. The results showed that although Tablolong Village generated slightly higher gross revenue, Oenaek Village demonstrated greater production efficiency. These differences were influenced by several factors, including seed quality, cultivation techniques, market accessibility, and natural resource management. The findings provide valuable insights for policymakers and stakeholders in developing strategies to improve the economic performance and livelihoods of seaweed farmers in both villages. Keywords: Kappaphycus alvarezii; seaweed farming; economic analysis; production efficiency; Tablolong Village; Oenaek Village.